2000
DOI: 10.1590/s1516-31802000000600010
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's sarcoma of the head and neck

Abstract: a b s t r a c tCONTEXT: Ewing's sarcoma is a rare neoplasm, which usually arises in long bones of the limbs and in flat bones of the pelvis, with the involvement of head and neck bones being very unusual.CASE REPORT: a case of Ewing's sarcoma occurring in the mandible of a 35-year-old female. Pain and swelling of the tumor were the main complaints. The early hypothesis was an undifferentiated malignant neoplasm, possibly a sarcoma. The CT scan depicted an expansive lesion, encapsulated, with septa and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…The intracytoplasmatic glycogen may be demonstrated by PAS stain in 75% of the cases, but it is not pathognomonic and conclusive because other small round cell may show the presence of glycogen as well (14,15). Due to similarity with many malignant tumors, the diagnosis of ES can be very difficult and the lesion must be differentiated from other small round cell tumors, such as small cell osteosarcoma, mesenchymal chondrosarcoma, embryonal rhabydomyosarcoma, neuroblastoma and lymphoma (1,16). The use of immunohistochemistry has helped in the diagnosis of this tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intracytoplasmatic glycogen may be demonstrated by PAS stain in 75% of the cases, but it is not pathognomonic and conclusive because other small round cell may show the presence of glycogen as well (14,15). Due to similarity with many malignant tumors, the diagnosis of ES can be very difficult and the lesion must be differentiated from other small round cell tumors, such as small cell osteosarcoma, mesenchymal chondrosarcoma, embryonal rhabydomyosarcoma, neuroblastoma and lymphoma (1,16). The use of immunohistochemistry has helped in the diagnosis of this tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that combined therapy including surgery, radiotherapy and chemotherapy is the best approach for ES (16). The multidisciplinary treatment protocols has dramatically improved the 5-year survival rate of patients with ES from less than 16% to more than 75% of cases (1,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, and most importantly, ES/pPNETs were often not separated from ES of the jaw and were reported together in case series and literature reviews (37,38). Thirdly, immunohistochemical and molecular genetic data that enable separation of central PNETs from peripheral PNETs were not reported in most cases, particularly those published before 2000 (37,39). Pooling of patient data would, however, enable such a comparison to be made, thereby identifying possible differences between ES and ES/pPNETs.…”
Section: Discussionmentioning
confidence: 99%
“…Intracytoplasmic glycogen is a definitive aspect, but not pathognomic because it is also present in other tumor cells, such as osteosarcomas, rhabdomyosarcomas and neuroblastomas. 12 Recent immunoperoxidase and cytogenic studies indicate that PNET and ES are the same entity showing varying degrees of neuroectodermal differentiaton and they are categorized into a group known as the Ewing family of tumors. CD 99/MIC2 is a cell surface glycoprotein found in virtually all ES and PNET.…”
mentioning
confidence: 99%